Security Based Intelligent Device in Wireless Sensor Network - Prasad Mishra, Laxmi; narayan Mohanty, Mihir (International Journal of Psychosocial Rehabilitation, 2025)
"Security" is one of the basic issues in a propelled neighbourhood condition. The present centre around research and formative issues of "Wireless Sensor Network (WSN)" based Smart Home. "Wireless Sensor Network (WSN)" based smart home detection device gives a protected and safe living environment. A "Wireless Sensor Network (WSN)" is a system that is developing by using tiny independent hubs (sensors). The inspiration is to display certain environmental parameters, such as, temperature, movement, dampness, sound, brilliance, weight, etc. This paper describes the improvement of a shrewd home environment based on the "Wireless Sensor Network (WSN)" and moreover delineates private essentialness watching and controlling tasks for smart home systems organization structure. This paper proposes an essential and flexible remote set up for “domestic’s computerization” of light, temperature, movement, moistness and gas by executing the dependable sensor hubs that could be controlled too watched. This development offers stimulating and new opportunity to construct the accessibility of devices within the home for "home computing".